STABILITY OF TREDECIC FUNCTIONAL EQUATION IN MATRIX NORMED SPACES - Pinelas, Sandra; RAMDOSS, MURALI; VEERAMANI, VITHYA (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
In this current work, we dene and nd the general solution of the tredecic functional equation. We also investigate and establish the generalized Ulam-Hyers stability of this functional equation in matrix normed spaces by using the xed point method.